INVESTIGATION OF EXTERNEL BONDED PATCH REPAIR OF LAMINATED COMPOSITE MATERIALS EXPERIMENTALY - Çetinkaya, Ali Şükrü; Pıhtılı, Hasım; Yıldırım, Hayri (My University, 2018)
For this study, woven glass and carbon fibres reinforced composite materialswere produced. Composite materials have been produced with eightlaminates. For experimental study, specimens with 10 mm internal hole wereprepared. Then, these specimens were repaired by using adhesive andcomposite patches with different repair parameters. Two different bondingpatch type were used for external bonding patch repair of the specimens.These were wet lay out patches and prepreg patches. Test specimens wereprepared in necessary curing temperatures and laboratory conditions. Byperforming the unidirectional tensile test to these specimens, the ultimatefailure loads of these repaired specimens were indicated. By comparing theseultimate failure loads of repaired specimens that prepared with variousparameters, the effects of several repair parameters on the ultimate failurestrength are investigated. These repair parameters are patch bonding area(D/W ratio), bonding length, adhesive thickness and patch thickness.
Keywords: Malzeme Bilimleri; Özellik ve Test; Malzeme Bilimleri; Kompozitler